Importance Of Information During Feasiiblity Study - Lee, Khong Ling (Universiti Sains Malaysia, 2007)
This research paper evaluates the importance of various types of information during a feasibility study based on the quantity surveyor’s point of view. The survey had been conducted with the co-operation of some selected consultancy practices in Penang Island, Malaysia. The primary purpose of this research is to identify the types of information needed to be determined during the feasibility study in order to let the quantity surveyor to be aware of the importance of information due to the projects’ development. Several types of information had been identified through the research, which consisting of site analysis, market analysis, economic analysis, financial analysis, design analysis and client’s requirement. The diversity of information play important roles in verifying the feasibility of a development project and each type of information contributes different effects to the feasibility report. Therefore, the most important type of information should be given prior consideration during the analysis stage. All of the information had been ranked according to their importance based on the quantity surveyor’s point of view.